Heat-induced hypervolemia: Does the mode of acclimation matter and what are the implications for performance at Tokyo 2020? - Kissling, L. S.; Akerman, A. P.; Cotter, J. D. (Temperature, 2020)
Tokyo 2020 will likely be the most heat stressful Olympics to date, so preparation to mitigate the effects of humid heat will be essential for performance in several of the 33 sports. One key consideration is heat acclimation (HA); the repeated exposure to heat to elicit physiological and psychophysical adaptations that improve tolerance and exercise performance in the heat. Heat can be imposed in various ways, including exercise in the heat, hot water immersion, or passive exposure to hot air (e.g., sauna). The physical requirements of each sport will determine the impact that the heat has on performance, and the adaptations required from HA to mitigate these effects. This review focuses on one key adaptation, plasma volume expansion (PVE), and how the mode of HA may affect the kinetics of adaptation. PVE constitutes a primary HA-mediated adaptation and contributes to functional adaptations (e.g., lower heart rate and increased heat loss capacity), which may be particularly important in athletes of "sub-elite" cardiorespiratory fitness (e.g., team sports), alongside athletes of prolonged endurance events. This review: i) highlights the ability of exercise in the heat, hot-water immersion, and passive hot air to expand PV, providing the first quantitative assessment of the efficacy of different heating modes; ii) discusses how this may apply to athletes at Tokyo 2020; and iii) provides recommendations regarding the protocol of HA and the prospect for achieving PVE (and the related outcomes).